FORMULATION AND EVALUATION OF EPIGALLOCATECHIN GALLATE AND BERBERINE-LOADED CHITOSAN NANOPARTICLES - SINDHURI, GOPU VIJAYA; MARIAPPAN, GURUSAMY; SUBRAMANIAN, SELVAMUTHUKUMAR (International Journal of Applied Pharmaceutics, 2023)
Objective: The current work aimed to prepare and characterize epigallocatechin gallate (EGCG)+berberine-loaded chitosan nanoparticle (EBNP). Methods: The ionic gelation method was adopted. A batch of 17 nanoformulations was prepared by using chitosan as a natural biodegradable polymer and EGCG+berberine as active drug content and characterised. Results: The SEM data proved that the chitosan-based nanoparticles were formed successfully with a spherical shape at 272 nm along with PDI 0.346. The FT-IR spectra confirmed that no drug-polymer interaction was observed. The DSC data proved that the formation of nanoparticles due to the presence of endothermic sharp melting points at 246 °C and 332 °C for EGCG and berberine in the pure form of the drug, whereas the same is absent in nanoformulation. The optimized formulation showed a percentage entrapment efﬁciency (% EE) for EGCG is 83.91 % and berberine at 90.62%, ZP of the nanoparticle is 11 mV. Conclusion: This study demonstrated that box–behnken designs can optimize the formulation and the process variables to achieve favorable responses. Hence, it can be concluded that the best-optimized nanoparticle formation was confirmed and characterized.